Relationship between biomechanical parameters techniques of the preliminary rotation among elite women hammers throwers - Vladyslav Rozhkov; Viktor Pavlenko; Yelena Pavlenko; Tatyana Pavlenko; Tetiana Shutieieva; Viacheslav Shutieiev (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the relationships technique of the first preliminary rotation with technique of the second preliminary swing elite women hummer throwers. Material and Methods: the research was attended by 8 hammer throwers (women) finalists' of European championships, and World championship during the 2016-2019 seasons. Research methods used: analysis and generalization of literary sources, processing video materials, methods of mathematical statistics. Results: very strong correlation was observed between times of the second preliminary rotation linear, angular velocities of the hammer, centrifugal force of the hammer at the end of the second preliminary rotation and angles in the right and left elbows at the end of the first preliminary rotation r=0,734-0,833. The correlation coefficient showed that if research women hummer throwers have more angles in the right and left elbows at the end of the first preliminary rotation they will have more time of the second preliminary rotation, linear, angular velocities of the hammer, centrifugal force of the hammer at the end of the second preliminary rotation. As a result correlations analysis was discovered that such parameters of technique first pre- rotation as: linear velocity of the hammer, angular velocity of the hammer, centrifugal force of the hammer, time of the first preliminary rotation don't have significant impact on the technique second pre-swing. Conclusions: the findings suggest established that for effective implementation second preliminary rotation during improvement technique of the first preliminary rotation the most attention should devote angles in the elbow joints, trajectory of the hammer, angle in the right knee and height lifting of the left heel from support at the end of the first preliminary rotation.